Evaluation of the development of competences in radiology and diagnostic imaging in a cross-sectional study in a medical graduation - Monteiro, Daniel Lucas Costa; Santos, Juliane Costa; Silva, Guilherme Alves da; Conceição, Alicia Renata Sales da; Lima, Kelyane Oliveira; Ribeiro, Samuel da Silva; Ribeiro, Emanuel da Silva; Freitas, Francisco Miguel da Silva; Silva, Marivaldo de Moraes e; Carodoso, José Ricardo Medeiros; Fernandes, Lucian Herlan da Costa Luz; Carodoso, Lara Rosa Cardoso e; et al. (International Journal of Advanced Engineering Research and Science, 2023)
To assess the development of skills by medical students in radiology and diagnostic imaging in a cross-sectional way in undergraduate medicine in an integrated and interdisciplinary curriculum. This is a quantitative, analytical, and expository cross-sectional study, through the application of a structured questionnaire on the radiological themes developed in the axis that has as practical support the Morphofunctional Laboratory, with students from the 1st, 5th and 8th semester of the medical course at the Centro Universitário Metropolitano da Amazônia (UNIFAMAZ), Belém, PA – Brazil. For the elaboration of the result of the present study, the analysis of 93 applied questionnaires was used, respecting the selection criterion, in which the questionnaire should contain the Free and Informed Consent Term duly completed and signed, of which 15 already had a previous graduation. The students at each end of the application of the questionnaire were more confident during the semesters, represented by the increasing average of correct answers over the semesters, and, in this way, corroborating the evolution of the students in the resolution and reasoning of the proposed questions. The information obtained from the medical students evaluated in the study corroborate that problem-based learning facilitates and assists in the process of obtaining knowledge, through the morphofunctional components of the course used to approach radiology and diagnostic imaging with a view multidimensional in addition to the role of complementary examination methods.